2000
DOI: 10.1007/s002210000395
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical contributions to working memory: evidence from event-related fMRI studies

Abstract: Working memory refers to the short-term retention of information that is no longer accessible in the environment, and the manipulation of this information, for subsequent use in guiding behavior. In this review, we will present data from a series of event-related functional magnetic-resonance-imaging (fMRI) studies of delayed-response tasks that were designed to investigate the role of different regions of the prefrontal cortex (PFC) during different working-memory component processes. From these data, we conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
270
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(306 citation statements)
references
References 46 publications
34
270
0
2
Order By: Relevance
“…In healthy controls, these regions are part of a neural network, which is thought to subserve manipulation during WM as well as covert subvocal rehearsal [Baddeley, 2003;D'Esposito et al, 2000]. The load-dependent patterns which were found in these cortical and subcortical areas suggest a linear relationship between WM demand and activation in patients, similar to the activation pattern found in controls subjects.…”
Section: Discussionmentioning
confidence: 63%
“…In healthy controls, these regions are part of a neural network, which is thought to subserve manipulation during WM as well as covert subvocal rehearsal [Baddeley, 2003;D'Esposito et al, 2000]. The load-dependent patterns which were found in these cortical and subcortical areas suggest a linear relationship between WM demand and activation in patients, similar to the activation pattern found in controls subjects.…”
Section: Discussionmentioning
confidence: 63%
“…These authors concluded that dorsolateral PFC is involved in both maintenance and manipulation. Similarly, D'Esposito, Postle, and Rympa (2000) found sustained activation in both aspects of the PFC for tasks requiring maintenance only and for tasks involving maintenance plus manipulation. Thus, it appears that the dorsolateral PFC is not only involved in executive processes, such as the manipulation and monitoring of information, but also may work in concert with the ventrolateral PFC during active maintenance.…”
mentioning
confidence: 76%
“…Executive control is thought to be embodied by the PFC; however, consensus regarding the loci of maintenance functions has not been reached so far. Some locate maintenance functions in posterior (parietal) regions of the brain, assigning the PFC a mediator role in controlling the information stored in those posterior areas (Knight & D'Esposito, 2003;Postle & Rypma, 2000;Curtis & D'Esposito, 2003;Postle, 2006). Others, in contrast, hypothesize dorsolateral regions to also reflect maintenance of online sensory representations per se (Cohen, Perlstein, Braver, Nystrom, Noll, Jonides, & Smith, 1997;Goldman-Rakic, 1987).…”
Section: The Prefrontal Cortexmentioning
confidence: 99%
“…However, in the light of an theory of WM as an non-modular, emergent property arising from the interaction of a highly distributed neural network advanced by some researchers (Postle, 2006;Hazy, Frank, & O'Reilly, 2006;D'Esposito, Postle, & Rypma, 2000;Collete et al, 2006, Miyake & Shah, 1999, we can make some observations, namely, that filtering out the acoustic features from the music in order to find the underlying WM main executive function might be the wrong approach to studying music-driven WM networks, and the only purpose of this subtraction operation, whereby the acoustic correlates are removed, is to observe the significant implication of the subcortical sensory subsystems co-responsible for WM retrieval, filtered out with the exclusion of the acoustic correlates that are necessary for the encoding of the memoranda they represent.…”
Section: Working Memory As An Emergent Temporal Integration Mechanismmentioning
confidence: 99%